2009
DOI: 10.1136/vr.165.20.589
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of MRSA types in slaughter pigs in different German abattoirs

Abstract: To investigate the prevalence of types of meticillin-resistant Staphylococcus aureus (MRSA) in slaughter pigs in German abattoirs, nasal swabs were collected from a total of 1026 pigs in five abattoirs after stunning in the course of two studies, and examined for MRSA. Study 1 included four abattoirs; study 2 was carried out in one large abattoir. Isolates were tested for antimicrobial susceptibility and characterised using spa-typing, multilocus sequence typing (MLST) and typing of the staphylococcal cassette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
49
5
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 16 publications
8
49
5
1
Order By: Relevance
“…Almost 37% of the isolates, 43% of them recovered from healthy carrier pigs, showed resistance to five or more classes of antimicrobials, whereas only 28% did in a study of 55 German ST398 isolates from diseased swine (21). All 100 isolates were resistant to tetracycline, a property of the ST398 clone also found by other authors (9,41). This resistance is mostly related to the presence of the tet(M) gene located in transposons Tn5801 and Tn916.…”
Section: Aac(6ј)-ie-aph(2љ)-ia Ant(4ј)-iamentioning
confidence: 59%
“…Almost 37% of the isolates, 43% of them recovered from healthy carrier pigs, showed resistance to five or more classes of antimicrobials, whereas only 28% did in a study of 55 German ST398 isolates from diseased swine (21). All 100 isolates were resistant to tetracycline, a property of the ST398 clone also found by other authors (9,41). This resistance is mostly related to the presence of the tet(M) gene located in transposons Tn5801 and Tn916.…”
Section: Aac(6ј)-ie-aph(2љ)-ia Ant(4ј)-iamentioning
confidence: 59%
“…The present study confirmed that experimental nasal colonization of pigs with MRSA does not result in clinical signs, despite a comparatively high bacterial load used for the inoculation. Pigs colonized with MRSA have been reported not to show clinical signs, so the term colonization instead of infection is currently used (13,35). The inoculation dose of ϳ5.0 ϫ 10 8 CFU/animal used in this study was determined in pretrials.…”
Section: Discussionmentioning
confidence: 99%
“…However, these are mainly field studies dealing with the prevalence of MRSA (14,28,35) in naturally contaminated animals on farms and in slaughterhouses. There are no reports about the rate of recovery of MRSA from internal organs of large domestic animals after experimental inoculation with MRSA.…”
mentioning
confidence: 99%
“…1]), which is often associated with this clonal type. It has been reported that MRSA ST398 carrying an SCCmec of type V has been the predominant livestock-associated MRSA clone in Europe (1,28), and a previous study of pigs and farm workers in Midwestern United States showed that the ST398 isolates were SCCmec type V (27).…”
Section: Figmentioning
confidence: 99%
“…Transmission of MRSA from colonized pigs to humans has been reported in The Netherlands (31). MRSA sequence type 398 (ST398) or clonal complex 398 (CC398) based on multilocus sequence typing (MLST), also referred to as livestock-associated MRSA (LA-MRSA), from pigs, pig farmers, and the environment has been reported in a number of European countries (5,8,9,10,14,19,28,31) and North America (18,22,27,34,35).…”
mentioning
confidence: 99%